High concentrations of persistent organic pollutants in adult killer whales (Orcinus orca) and a foetus stranded in Ireland. (February 2020) - Schlingermann, Moira; Berrow, Simon; Craig, Darren; McHugh, Brendan; Marrinan, Michael; O'Brien, Joanne; O'Connor, Ian; Mudzatsi, Engelberth; White, Philip
Abstract: Bio-accumulation of persistent organic pollutants including polychlorinated biphenyls (PCBs), brominated flame retardants and organochlorine pesticides continue to be of major concern for marine apex predators such as killer whales. The concentrations of 16 polychlorinated biphenyls, 7 poly-brominated diphenyl ethers (PBDEs), 1 poly-brominated biphenyl (PBB) and a range of 19 organochlorine compounds (OCs) was investigated in blubber samples from a mother-foetus pair, an adult female and an adult male killer whale stranded in Ireland between 2010 and 2017. Concentrations ranged from 1.5 mg/kg to 49.3 mg/kg lipid weight and 0.04–1.2 mg/kg lipid weight for Σ16PCBs and Σ7PBDEs respectively. Concentrations of organochlorine compounds were also investigated in the male killer whale; a Σ19OC concentration of 49.4 mg/kg lipid weight was recorded. This study shows high levels of persistent organic pollutants occur in this species of whales stranded in Ireland. Highlights: Contaminant data for a sparsely studied region has been expanded. Provides information regarding the rare stranding of mother-foetus killer whale pair. Persistent organic pollutant threshold exceeded in Irish killer whale stranding.